Bringing Machine‐Learning Enhanced Quantum Chemistry and Microwave Spectroscopy to Conformational Landscape Exploration: the Paradigmatic Case of 4‐Fluoro‐Threonine. Issue 24 (20th March 2023) - Barone, V.; Fusè, M.; Aguado, R.; Potenti, S.; León, I.; Alonso, E. R.; Mata, S.; Lazzari, F.; Mancini, G.; Spada, L.; Gualandi, A.; Cozzi, P. G.; et al.
Abstract: A combined experimental and theoretical study has been carried out on 4‐fluoro‐threonine, the only naturally occurring fluorinated amino acid. Fluorination of the methyl group significantly increases the conformational complexity with respect to the parent amino acid threonine. The conformational landscape has been characterized in great detail, with special attention given to the inter‐conversion pathways between different conformers. This led to the identification of 13 stable low‐energy minima. The equilibrium population of so many conformers produces a very complicated and congested rotational spectrum that could be assigned through a strategy that combines several levels of quantum chemical calculations with the principles of machine learning. Twelve conformers out of 13 could be experimentally characterized. The results obtained from the analysis of the intra‐molecular interactions can be exploited to accurately model fluorine‐substitution effects in biomolecules. Abstract : Fluorinated α ‐amino acids have been attracting increasing attention, but their structure in the gas‐phase has not been investigated yet. Fluorination has a negligible impact on steric properties, but has a dramatic effect on the electronic properties. 4‐fluoro‐threonine has been efficiently synthesized in large amount and its conformational landscape has been disentangled through a combination of experiment and theory beyond the state of the art.